Territorial planning and sustainable development—case study: Protected areas in the territory of the Aspiring West Geopark, Portugal - Alline Dias; Rafael Robina-Ramírez; Marcelo Sánchez-Oro Sánchez (Frontiers in Environmental Science, 2023)
Introduction: The holistic concept of the sustainable development of United Nations Educational, Scientific and Cultural Organization (UNESCO) Global Geoparks encompasses the promotion of connected protected areas and activities that link geological heritage with other aspects of natural and cultural heritage. This case study aims to identify points of articulation and/or to identify conflicts in the overlap between protected areas and UNESCO World Geoparks in Portugal, and to provide information to improve the interrelation of these designations.Methods: The methodological procedures in analysing the organisational structures of different classified areas from the respective management documents. The technical procedure consisted of document consultation and on-site activities carried out between September 2020 and November 2021.Results: The study resulted in the identification of points of natural objects that can be held together by protected natural spaces and aspiring Oeste Geopark. A proposal for synergistic action was presented, with the main pillars of integration in the territory. The different designations for sustainable territorial management in complementary to the conservation of natural heritage. The results of the analyses indicate that the overlap of the different designations of areas and territories studied here can act both in a joint and complementary way to conserve natural heritage.Discussion: This reinforcement study, which has different designations of areas and/or territories for sustainable territorial planning at the local, regional, national, and international levels, is fundamental for nature conservation, lacking more in terms of efficient management and integration of the social component.